Cause or effect: What matters?: How 12-month-old infants learn to categorize artifacts - Träuble, Birgit; Pauen, Sabina (The British journal of developmental psychology, 2011)
This paper investigates the role of cause and effect relations for infants' learning about artifacts. Two experiments tested whether 12-month-olds categorized a given set of unfamiliar artifacts according to overall similarity and/or according to part similarity, depending on what kind of video demonstration was presented before the start of the categorization task. In both experiments, the actions performed with objects were accompanied by interesting effects but the causal relation between object-structure and effects was teased apart. In one video demonstration (Expt 1), the experimenter used the object part to produce some kind of effect in a causally plausible way. In another video demonstration (Expt 2), the experimenter performed similar actions with the same objects as in Expt 1, followed by the same effects as before. Importantly, however, no plausible cause-effect relation was provided this time. Only infants participating in Expt 1 categorized the set of unfamiliar objects according to part similarity. This finding suggests that 12-month-olds attend to the causal relation between specific object parts and their functional use when categorizing artifacts, rather than merely associating form-characteristics with an interesting effect.